A decade of in situ cosmogenic 14C in Antarctica - Keir Alexander Nichols (Annals of Glaciology, 2022)
Cosmogenic nuclide measurements in glacial deposits extend our knowledge of glacier chronologies beyond the observational record. The short half-life of in situ cosmogenic 14C makes it particularly useful for studying glacier chronologies, as resulting exposure ages are less sensitive to nuclide inheritance when compared with more commonly measured, long-lived nuclides. An increasing number of laboratories using an automated process to extract carbon from quartz has led to in situ 14C measurements in Antarctic samples at an accelerating rate over the past decade, shedding light on deglaciation in Antarctica. In situ 14C has had the greatest impact in the Weddell Sea Embayment, where inferences on the thickness of ice and timing of deglaciation were limited by inheritance in other cosmogenic nuclide systems. Future subglacial measurements of the nuclide hold much potential as they can provide direct evidence of proposed Holocene thinning and subsequent re-thickening of parts of the Antarctic ice sheets.